Left Prefrontal Cortex Supports the Recognition of Meaningful Patterns in Ambiguous Stimuli - Bartel, Grégory; Marko, Martin; Rameses, Imani; Lamm, Claus; Riečanský, Igor (Frontiers in Neuroscience, 2020)
Processing of ambiguous visual stimuli has been associated with an increased activation of the left lateral prefrontal cortex (PFC) in neuroimaging studies. Nevertheless, the functional role of prefrontal activity in this process is not fully understood. In this experiment we asked participants to evaluate ambiguous inkblots from the Rorschach test, while stimulating the left lateral PFC using excitatory anodal transcranial direct current stimulation (tDCS). In addition, visual insight ability was assessed as a control measure requiring visual and conceptual restructuration and convergent thinking rather than divergent idea generation employed to interpret the equivocal Rorschach inkblots. Using a randomized double-blind design, we demonstrated that anodal tDCS increased the number of meaningful patterns recognized in the inkblots but had no significant effect on visual insight. These findings support the role of left lateral PFC in the processing of ambiguous visual information and object recognition. More generally, we discuss that the PFC may be involved in the mechanisms supporting the activation of stored visual and semantic representations in order to compensate for less informative bottom-up inputs and thus facilitate flexible cognition and idea generation.